Yanggan Yizhong decoction prevents liver metastasis from colorectal cancer by targeting myeloid-derived suppressor cells through the regulation of bile acid metabolism in the gut microbiota - Xie, Hongting; Zhu, Shijie; Xue, Peng; Xie, Feiyu; Zhao, Leyi; Chu, Xuelei (Frontiers in Microbiology, 2025)
IntroductionLiver metastasis (LM) exhibits a high incidence in colorectal cancer (CRC), yet effective preventive therapies are still lacking. Based on the prophylactic principle of harmonizing the liver and spleen, Yanggan Yizhong (YGYZ) decoction has shown clinical effectiveness in preventing LM. This study aims to explore the active components and underlying mechanisms of YGYZ in the prevention and treatment of LM.MethodsThe components of YGYZ were analyzed using Ultra-High Performance Liquid Chromatography coupled with High-Resolution Tandem Mass Spectrometry (UPLC-HR-MS/MS). The LM mouse model was established through intrasplenic injection of ct26-luc cells to evaluate the effect and safety of YGYZ on LM. Fecal microbiota transplantation (FMT) was performed to create microbiota-altered mice, and liver tissue morphology along with HE staining was utilized to dynamically monitor LM progression. Flow cytometry and inflammatory factor assays were conducted to assess the immune microenvironment (IME) of the liver pre-metastatic niche (PMN). Additionally, 16S rRNA sequencing and bile acid (BA) metabolomics were employed to investigate the role of YGYZ in modulating gut microbiota (GM) and BA. Western blot analysis was performed to identify key targets of YGYZ in the GM-BA-immunity pathway.ResultsUPLC-HR-MS/MS analysis identified 95 compounds in YGYZ, Glycyrrhizic acid, Bergapten, and Icariin as the main compounds. YGYZ and its FMT inhibited LM of CRC with safety, inhibited CD11b+Ly6G+ and CD11b+Ly6C+ cells in the pre-metastatic stage, decreased CD11b+Ly6G+ cells in the metastatic stage, reduced immunosuppressive factors such as Arg-1, TGF-β, and IL-10, and improved the CD4+/CD8+ T-cell ratio, regulating liver PMN. YGYZ also improved the GM structure, particularly decreasing the abundance of Clostridium in the LM mice. For the hepatic BAs profile, YGYZ increased the content of primary BAs—Nor cholic acid (NorCA), Taurocholic acid, Taurochenodeoxycholic Acid, and Tauro β-Muricholic Acid, and secondary BAs—ursodeoxycholic acid (UDCA), with similar trends in FMT, while YGYZ decreased NorCA, α-Muricholic acid, Tauro α-Muricholic acid, and UDCA in the fecal BA profile. YGYZ and its FMT dampened the protein expression of IL-6, STAT3, and pSTAT3, but only YGYZ downregulated kruppel-like factor 15 (KLF15).ConclusionYGYZ may prevent LM by remodeling the GM and synergistically inhibiting KLF15 to regulate the enterohepatic BA cycle, and suppressing the proliferation and activation of myeloid-derived suppressor cells through the IL-6/STAT3 pathway, thereby improving IME of liver PMN.